An unusual appearance of a serous ovarian cyst coexisting with endometriosis: A case report. (2020) - Naem, Antoine; Kouba, Lamia; Al-Kurdy, Bashar
Highlights: Fibrosis is a significant complication of endometriosis, provoked mainly by TGF-β. Endometriosis-induced fibrosis may alter the known morphology of the ovarian cysts. The mural fibrosis may reflect unrecognized fibrosis within the ovarian stroma. Endometriosis may have potential fibrotic effects on the ovarian stroma. Ovarian stromal fibrosis could contribute to the endometriosis-related infertility. Abstract: Introduction: Endometriosis is an estrogen-dependent disease that can provoke fibrosis through the elevated concentration of TGF-β. Endometriosis-related fibrosis often manifests as pelvic adhesions, and it is almost always observed microscopically when examining the endometriotic lesions. Here we are reporting, for the first time in literature, an unusual gross appearance of a serous ovarian cyst that coexisted with endometriosis. Presentation of case: A 32-year-old G1P2 woman presented to our hospital complaining of the inability to conceive. She was scheduled to have an exploratory laparoscopy. Upon reaching the abdominal cavity, several islands of endometriosis and a left ovarian mass were spotted. The ovarian mass was resected by an excisional biopsy and the pathologic examination showed a benign ovarian cyst with extreme fibrosis in its wall. Discussion: Endometriosis often induces a chronic pelvic inflammation, mediated mainly by the over-activated macrophages. These cells secrete many cytokines and growth factors that alter the normal pelvic milieu. TGF-β levels are often elevated within the peritoneal fluid, which stimulate fibroblasts and provoke tissue fibrosis. One study suggested that ovarian stromal fibrosis can induce infertility by impairing folliculogenesis. LH-inhibiting regimens can reverse the stromal fibrosis, and improve the fertility outcomes. Conclusion: The mural fibrosis seen in the cystic wall reflects unrecognized ovarian stromal fibrosis induced by the fibrogenic effects of endometriosis. This process may play a potential role in provoking infertility in patients with endometriosis, and could be reversed by administrating the LH-inhibiting regimens.